2021
DOI: 10.1371/journal.pone.0240770
|View full text |Cite|
|
Sign up to set email alerts
|

Evolutionary history of Carnivora (Mammalia, Laurasiatheria) inferred from mitochondrial genomes

Abstract: The order Carnivora, which currently includes 296 species classified into 16 families, is distributed across all continents. The phylogeny and the timing of diversification of members of the order are still a matter of debate. Here, complete mitochondrial genomes were analysed to reconstruct the phylogenetic relationships and to estimate divergence times among species of Carnivora. We assembled 51 new mitogenomes from 13 families, and aligned them with available mitogenomes by selecting only those showing more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 116 publications
5
57
0
1
Order By: Relevance
“…For comparison, the values in blue are mean ages estimated using a log normal prior distribution for fossil calibration points ("L approach"; see main text for details and discussion). Species names follow the classification of the IUCN [1]; the name of the taxa written in red have been changed following our results which suggest these taxonomic changes (see the discussion for details).…”
Section: Figmentioning
confidence: 61%
See 1 more Smart Citation
“…For comparison, the values in blue are mean ages estimated using a log normal prior distribution for fossil calibration points ("L approach"; see main text for details and discussion). Species names follow the classification of the IUCN [1]; the name of the taxa written in red have been changed following our results which suggest these taxonomic changes (see the discussion for details).…”
Section: Figmentioning
confidence: 61%
“…The two outgroup species are not shown. Species names follow the classification of the IUCN [1]; the taxa written in red highlight the taxonomic issues discussed in the main text. The accession numbers of the 42 mitogenomes of Carnivora specially sequenced for this study are indicated in red.…”
Section: Canis Latrans Nc 008093mentioning
confidence: 99%
“…Complete mitochondrial genome datasets provide a robust phylogeny with highly resolved trees having strong branch support [40]. However, the mitochondrial genomes can conflict with a phylogeny estimated from the nuclear genome due to the replacement of organelle genomes from one species or populations with those of another mediated by hybridization and introgression [41][42][43][44]. The use of mitochondrial genome datasets may also provide evidences of adaptive radiations, as signatures of selection were detected during reconstructing mitochondrial genome phylogenies for the number of vertebrate taxa including deep-sea fishes [45,46], marine turtles [47,48], and mammals [49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum age is inferred by an additional fossil age older than that speci c node (and the minimum age), i.e., the stem age (or the parent node age at an edge) is representative, although the de nition is sometimes unclear and controversial. Minimum ages are generally more accurate and reliable than maximum ages (Hassanin et al, 2021). In actual mammalian MCMCTree analyses (dos Reis et al, 2012(dos Reis et al, , 2018, a speci c node age (posterior divergence time) is estimated by prior divergence time applying minimum and maximum ages, although maximum age is only roughly estimated (named soft maximum bound).…”
Section: Fossil Calibration Protocols: Competition Between Beast and Mcmctree (Table 1)mentioning
confidence: 99%
“…Application of genome-scale sequence data may be better as dos Raise et al ( 2012) did so, but in the present case unrelated to the precision of node dating, calibration method is much more important. Hassanin et al (2021) applied a lognormal distribution on the calibrated node ages and compared it to the uniform distribution for the minimum and maximum age sets. In BEAST v.1 X, considering maximum ages, we tried to select lognormal for prior distribution to construct Fig.…”
Section: Inconsistent Mammalian Base Substitution Ratementioning
confidence: 99%